An All Too Radical Solution to the Problem of Evil: a Reply to Harrison - Linford, Dan (Sophia, 2018)
Gerald Harrison has recently argued the evidential problem of evil can be resolved if we assume the moral facts are identical to God's commands or favorings. On a theistic metaethics, the moral facts are identical to what God commands or favors. Our moral intuitions reflect what God commands or favors for us to do, but not what God favors for Herself to do. Thus, on Harrison's view, while we can know the moral facts as they pertain to humans, we cannot know the moral facts as they pertain to God. Therefore, Harrison argues, the evidential problem of evil inappropriately assumes God to be intuitively moral, when we have no reason to suppose a perfectly good being would match the expectations provided by our moral intuitions. Harrison calls his view a new form of skeptical theism. In response, I show Harrison's attempt to dissolve the problem of evil exacerbates well-known skeptical consequences of skeptical theism. Harrison's new skeptical theism leaves us with problems motivating a substantive religious life, the inability to provide a variety of theological explanations, and, despite Harrison's comments to the contrary, worsens problems having to do with the possibility of divine deception.